2019
DOI: 10.3390/agriculture9030056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil pH and Fertilizers on Haskap (Lonicera caerulea L.) Vegetative Growth

Abstract: Haskap (Lonicera caerulea L.) is a new northern latitude fruit crop that is increasing in popularity. This sudden enthusiasm for haskap increases the need for obtaining baseline knowledge related to establishing it as a crop, such as its optimal soil pH and fertilizer needs. In a greenhouse, one-year-old haskap plants (cultivar: Indigo Treat©) were grown in a local loamy sand. We assessed the impact of pH and fertilizer on haskap vegetative growth through an experiment involving four soil pH and five fertiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…The pH is one of the most important soil properties. Many studies have shown that soil pH is a major driver for the assembly of soil bacterial and fungal microbiotas 60 62 . Soil pH was the major driver in the early growth stage, which should be an important factor to be considered when choosing the bed soil for the seedling growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH is one of the most important soil properties. Many studies have shown that soil pH is a major driver for the assembly of soil bacterial and fungal microbiotas 60 62 . Soil pH was the major driver in the early growth stage, which should be an important factor to be considered when choosing the bed soil for the seedling growth.…”
Section: Discussionmentioning
confidence: 99%
“…Soil pH was the major driver in the early growth stage, which should be an important factor to be considered when choosing the bed soil for the seedling growth. For example, soil pH was assessed in the farmland of tomato 63 , maize 64 and haskap 60 . In our study, only the pH of astragalus-cultivated soils was shown to be closely connected to the bacterial and fungal microbiotas, as confirmed by Mantel test and Envfit test.…”
Section: Discussionmentioning
confidence: 99%